INCREASING SOCIAL LEARNING RESULT IN GLOBALIZATION SUBJECT WITH APPLYING GUIDED INQUIRY LEARNING METHOD TO SIXTH GRADE STUDENTS OF PAKUHAJI ELEMENTARY SCHOOL - Fauzia Fauzia; Siti Hasanan Nurparihat; Deden Herdiana Altaftazani (IKIP Siliwangi, 2018)
The background of this research is observation result on Social learning process in Pakuhaji Elementary School on Ngamprah subdistrictin West Bandung region, where the learning process still classicalwhere teacher become the center of learning and the teacher is too text book which is caused the student activity is very less and make the learning process become unpleasant, so the student learning result cannot be optimum. The method used in this research is classroom action research. The data collection done with the observation and learning result test. The reseach done in three cycles that is precycle, first cycle and second cycle. In precycle the average of the class is 64.35, with 11 students who thorough, then in fisrt cycle the average of the class is 79.39 up significantly with 26 students who thorough, next in second cycle with the average of the class is 87.55 with 28 students who thorough. From the number of student who reach Minimum Competence Criteria, there is a raising from 11 students or 34.48% from all of student now become 28 students or 90.32% from all of student, which is 31 students. From this research result shows that applying inquiry learning method can increase students learning result in Globalization subject.The background of this research is observation result on Social learning process in Pakuhaji Elementary School on Ngamprah subdistrictin West Bandung region, where the learning process still classicalwhere teacher become the center of learning and the teacher is too text book which is caused the student activity is very less and make the learning process become unpleasant, so the student learning result cannot be optimum. The method used in this research is classroom action research. The data collection done with the observation and learning result test. The reseach done in three cycles that is precycle, first cycle and second cycle. In precycle the average of the class is 64.35, with 11 students who thorough, then in fisrt cycle the average of the class is 79.39 up significantly with 26 students who thorough, next in second cycle with the average of the class is 87.55 with 28 students who thorough. From the number of student who reach Minimum Competence Criteria, there is a raising from 11 students or 34.48% from all of student now become 28 students or 90.32% from all of student, which is 31 students. From this research result shows that applying inquiry learning method can increase students learning result in Globalization subject.